Salmonella infection as a trigger for Polyarteritis Nodosa - Pedro Neves Tavares; Patricia Alves; Rita Lizardo Grácio; Paula Gonçalves Costa; Carla Falcão; Catarina Duarte Santos; Filipa Amado (European Journal of Case Reports in Internal Medicine, 2020)
Polyarteritis nodosa is a systemic necrotizing vasculitis that typically affects medium-sized muscular arteries, with occasional involvement of small muscular arteries. Most cases of polyarteritis nodosa are idiopathic but multiple infectious agents have been associated with this disease. We present a clinical case of a 72-year-old male with fever, diarrhoea and haemodynamic instability, diagnosed with a bacterial infection caused by Salmonella Typhi. One week after clinical resolution of the infection, the patient developed purpuric lesions with ulcers, pustules and necrotic areas accompanied by testicular pain and weight loss of 5 kg over the previous 15 days. A skin biopsy was performed and it revealed typical histologic signs of polyarteritis nodosa. The aetiologic association between bacteria of the genus Salmonella and polyarteritis nodosa has been previously described in the scientific literature but seldom meeting classification criteria and with histologic confirmation.